RecutClub 2.0: Deployment of a Trainee-Led, Didactic-Centered Whole Slide Imaging Platform. (9th November 2022) - Hsu, Jim; Christensen, Paul; Long, Scott
Abstract: Objectives: The Houston Methodist Pathology training program encourages trainee participation in quality improvement (QI) projects for improving the didactics experience. One of these initiatives is RecutClub, a whole slide imaging (WSI) web-based platform for presenting surgical pathology unknown conference cases. With the evolving nature of pathology didactics in an ever-changing world where remote work plays an increasingly important role, several refinements were needed to ensure that the platform could continue to provide an unparalleled WSI experience for incoming trainees. Additionally, the burden of updating site content needed to be distributed from the site administrators to the end-users. Methods: RecutClub is operated through Google Cloud via a Google App Engine instance. It connects to Google Cloud Databases to store persistent tabular data and Google Cloud Storage for pyramidal JPEG files used to display whole slide images in a web-browser. In the next generation platform (RecutClub 2.0), the largest change was to migrate case uploading from a developer-controlled solution to a decentralized, trainee-driven web portal. To ensure a superior user experience, the entire site as well as the upload form was migrated to Bootstrap 4. An AJAX-native, asynchronous uploader was built to interface the existing Google Cloud platform to a new upload portal that allows authorized trainees to build cases from scratch. Additionally, a tagging solution was implemented to allow for server-side persistent storage of trainee-selected cases, such as "interesting" cases or cases for further review. This tagging complements the existing region of interest (ROI) and case search functionalities. Results: The deployment of RecutClub 2.0 involved multiple rounds of resident-led testing and feedback. Several regular testers offered ongoing user feedback and suggestions for visual layout and usability. The response from the general trainee population after deployment was overwhelming positive, with many trainees commenting on the "improved" visual aesthetics as well as the convenience of the upload functionality. Administrator involvement in case-upload time decreased from 2 hours/month to 0 hours/month due to enabling trainee-driven uploading. Conclusions: The deployment of RecutClub 2.0 fulfilled the dual primary objectives of enabling straightforward trainee-led content updates, as well as decreasing administrator involvement in case-upload time. These and other changes ensure that RecutClub can continue to provide an unparalleled WSI experience for pathology trainees at Houston Methodist, while also providing fresh content in a landscape with several competing WSI platforms.